SYNERGY-Everolimus-Eluting Stent With a Bioabsorbable Polymer in ST-Elevation Myocardial Infarction: CLEAR SYNERGY OASIS-9 Registry - Jolly, Sanjit S; Lee, Shun Fu; Mian, Rajibul; Kedev, Sashko; Lavi, Shahar; Moreno, Raul; Montalescot, Gilles; Hillani, Ali; Henry, Timothy D; Asani, Valon; Storey, Robert F; Silvain, Johanne; et al. (Elsevier BV, 2024)
Our objective was to evaluate the clinical effectiveness of the SYNERGY stent (Boston Scientific Corporation, Marlborough, Massachusetts) in patients with ST-elevation myocardial infarction (STEMI). The only drug-eluting stent approved for treatment of STEMI by the Food and Drug Administration is the Taxus stent (Boston Scientific) which is no longer commercially available, so further data are needed. The CLEAR (Colchicine and spironolactone in patients with myocardial infarction) SYNERGY stent registry was embedded into a larger randomized trial of patients with STEMI (n = 7,000), comparing colchicine versus placebo and spironolactone versus placebo. The primary outcome for the SYNERGY stent registry is major adverse cardiac events (MACE) as defined by cardiovascular death, recurrent MI, or unplanned ischemia-driven target vessel revascularization within 12 months. We estimated a MACE rate of 6.3% at 12 months after primary percutaneous coronary intervention for STEMI based on the Thrombectomy vs percutaneous coronary intervention alone in STEMI (TOTAL) trial. Success was defined as upper bound of confidence interval (CI) to be less than the performance goal of 9.45%. Overall, 733 patients were enrolled from 8 countries with a mean age 60 years, 19.4% diabetes mellitus, 41.3% anterior MI, and median door-to-balloon time of 72 minutes. The MACE rate was 4.8% (95% CI 3.2 to 6.3%) at 12 months which met the success criteria against performance goal of 9.45%. The rates of cardiovascular death, recurrent MI, or target vessel revascularization were 2.7%, 1.9%, 1.0%, respectively. The rates of acute definite stent thrombosis were 0.3%, subacute 0.4%, late 0.4%, and cumulative stent thrombosis of 1.1% at 12 months. In conclusion, the SYNERGY stent in STEMI performed well and was successful compared with the performance goal based on previous trials.
Keywords: drug-eluting stent; PCI; STEMI